"Microplastic seasoning": A study on microplastic contamination of sea salts in Bangladesh - Siddique, Mohammad Abdul Momin; Uddin, Azad; Hossain, Md Soliman; Rahman, Shahriar Md Arifur; Rahman, M Safiur; Kibria, Golam; Malafaia, Guilherme (Marine pollution bulletin, 2024)
This study investigated microplastics (MPs) in commercial sea salts from Bangladesh. The presence of MPs in the 18 sea salt bands was 100 %, where the mean MPs abundance was 471.67 MPs/kg, ranging between 300 and 670 MPs/kg. The maximum number of MPs in the 300-1500 μm size class was significantly higher than the 1500-3000 μm and 3000-5000 μm size class. The most dominant color was black. Fibers and foams were the dominant shapes. The highest number of MPs was 41 %, obtained from coarse salt grains. Four types of polymers were mainly identified from the analyzed samples: PP, PE, PET, and PA. The mean polymer risk index value among these sea salts was 539 to 1257. The findings of this study can be helpful for consumers, salt industries, and policymakers to be aware of or reduce MP contamination levels in sea salts during production and consumption.
Keywords: Bangladéš; kuchyňská sůl; Salts; Microplastic; soli; Plastics; plastické hmoty; Environmental Monitoring; Commercial salt; mikroplasty; Contamination; monitorování životního prostředí; Health risk; Sodium Chloride, Dietary; Water Pollutants, Chemical; Bangladesh; Table salt; Microplastics; chemické látky znečišťující vodu